American Thyroid Association ultrasound system for the initial assessment of thyroid nodules: Use in stratifying the risk of malignancy of indeterminate lesions. Issue 4 (16th December 2017) - Trimboli, Pierpaolo; Deandrea, Maurilio; Mormile, Alberto; Ceriani, Luca; Garino, Francesca; Limone, Paolo P.; Giovanella, Luca
Abstract: Background: The ultrasound risk stratification system of the American Thyroid Association (ATA) is frequently adopted in clinical practice. Here, we evaluated its performance in a series of nodules with indeterminate fine‐needle aspiration cytology (FNAC) report. Methods: Indeterminate thyroid nodules diagnosed at 2 medical centers were retrospectively screened, ultrasound images were reevaluated, and lesions were classified according to the ATA. Single ultrasound parameters were also analyzed. Results: One hundred seventy‐three indeterminate lesions were included with 24.8% of malignancy. The high suspicion class showed a cancer rate (75%) significantly ( P < .001) higher than that recorded in the other categories (16.8%). Between ultrasound parameters, halo and microcalcifications were the most sensitive and specific ones. The most accurate receiver operating characteristic (ROC)‐derived cutoff of nodule's diameter was >4.1 cm. At multivariate analysis, only the ATA class of high suspicion and size >4.1 cm were significantly associated with cancer (odds ratios [ORs] 19.4 and 5.4, respectively). Conclusion: The ATA ultrasound system is reliable in the risk stratification of indeterminate thyroid lesions.